1981
DOI: 10.2172/5555056
|View full text |Cite
|
Sign up to set email alerts
|

Review of operating experience at the Los Alamos Plutonium Electrorefining Facility, 1963-1977

Abstract: under contract W-7405-ENG-36.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Electrorefining was further developed to process several kilogram amounts of impure plutonium at a time. 83,84,[86][87][88] Instead of operating the cell under at constant 2 V, reaction cells were run at constant current. Initial trials showed currents above 6 amps resulted in tantalum contamination in the product due to dissolution of the tantalum stirrer/anode.…”
Section: 3) Electrorefiningmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrorefining was further developed to process several kilogram amounts of impure plutonium at a time. 83,84,[86][87][88] Instead of operating the cell under at constant 2 V, reaction cells were run at constant current. Initial trials showed currents above 6 amps resulted in tantalum contamination in the product due to dissolution of the tantalum stirrer/anode.…”
Section: 3) Electrorefiningmentioning
confidence: 99%
“…86 As a result, MgO stirrers were used and a separate anode rod with ceramic sheath was used to pass higher currents through the molten anode material. 82,[86][87][88] Additionally, MgO crucibles were used due to their increased availability, and thus reduced the amount of Al contamination in the product. 8621 During electrorefining as the amount of plutonium in the anode decreases, the concentration of impurities increases and increases the melting point of the anode slag.…”
Section: 3) Electrorefiningmentioning
confidence: 99%
“…In the ER process, liquid plutonium oxidizes from the anode ingot into a molten-salt electrolyte where the Pu(III) ion is transported through the salt to the cathode, where it is reduced back to metal (53,58). The liquid metal drips off the cathode and into the annular space to produce an annular metal casting, or ER ring.…”
Section: Separation and Purification From Irradiated Uraniummentioning
confidence: 99%
“…added is determine'., by the requirements for americium removal. (For a detailed discussion of t.'.is point, see Ref 1…”
mentioning
confidence: 96%